Los patios divertidos en Secundaria y Técnico en Animación de Actividades Físicas y Deportivas: una experiencia a través del Aprendizaje Servicio. - Torres-Garcia, Sheila; Valverde-Esteve, Teresa; Salvador-García, Celina (Aula abierta, 2022)
Patios divertidos fue un proyecto de Aprendizaje Servicio desarrollado con el fin de fomentar las relaciones interpersonales de un grupo de alumnado de Educación Secundaria Obligatoria (ESO). Se muestran los efectos generados en el alumnado de ESO y del estudiantado del ciclo superior en Técnico en Animación de Actividad Físicas y Deportivas (TAFAD) sobre las dimensiones de socialización, amistad, utilidad, conflictos y aprendizaje tras la puesta en práctica. Se concluye que el proyecto realizado ha cumplido con los objetivos: mejorar los procesos de socialización, integración e inclusión del alumnado de ESO, así como la formación integral del alumnado de TAFAD.
Patios divertidos in Secondary and Vocational Training: an experience through Service-Learning
Patios divertidos ("Engaging recesses") was a Service-Learning project aimed at improving social relationships among a group of secondary school students (ESO). By means of this project, students of a higher-level training course in Sporting and Physical Activities (TAFAD in Spanish) were able to apply curricular contents while attending a social need. The objective of this paper is to present this experience and analyse the views of the participants regarding its effects on the following dimensions: socialisation, friendship, utility, conflicts and learning. We used a descriptive-exploratory qualitative approach in order to analyse 13 interviews (1 teacher, 6 ESO students and 6 TAFAD students). We conclude that the project has achieved its objectives: to improve ESO students' socialisation, integration and inclusion, as well as promote the integral development of TAFAD students.
Keywords: aprendizaje-servicio; metodología; socialización; educación; service-learning; methodology; socialization; education; Emerging; Scopus